Structural complexity of a composite amyloid fibril - Lewandowski, Józef R. (2011)
The molecular structure of amyloid fibrils and the mechanism of their formation are of substantial medical and biological importance, but present an ongoing experimental and computational challenge. An early high-resolution view of amyloid-like structure was obtained on amyloid-like crystals of a small fragment of the yeast prion protein Sup35p: the peptide GNNQQNY. As GNNQQNY also forms amyloid-like fibrils under similar conditions, it has been theorized that the crystal's structural features are shared by the fibrils. Here we apply magic-angle-spinning (MAS) NMR to examine the structure and dynamics of these fibrils. Previously multiple NMR signals were observed for such samples, seemingly consistent with the presence of polymorphic fibrils. Here we demonstrate that peptides with these three distinct conformations instead assemble together into composite protofilaments. Electron-microscopy (EM) of the ribbon-like fibrils indicates that these protofilaments combine in differing ways to form striations of variable widths, presenting another level of structural complexity. Structural and dynamical NMR data reveal the presence of highly restricted side chain conformations involved in interfaces between differently structured peptides, likely comprising interdigitated steric zippers. We outline molecular interfaces that are consistent with the observed EM and NMR data. The rigid and uniform structure of the GNNQQNY crystals is found to contrast distinctly with the more complex structural and dynamic nature of these “composite” amyloid fibrils. These results provide insight into the fibril-crystal distinction and also indicate a necessary caution with respect to the extrapolation of crystal structures to the study of fibril structure and formation.